A Cytokine/Bradykinin Storm Comparison: What Is the Relationship Between Hypertension and COVID-19?. (20th April 2021) - Wilczynski, Stephanie A; Wenceslau, Camilla F; McCarthy, Cameron G; Webb, R Clinton
Graphical Abstract: